Study on management strategy of the on-street parking in Urban Residential Area - Taking Harbin as an Example. Issue 1 (March 2021) - Xiaoyan, Zhu; Xiqiao, Zhang; Xu, Sun
Abstract: On road parking is a necessary supplementary form to solve the urban parking problem, which plays an important part in alleviating the parking demand pressure in residential areas. However, due to the poor management and use of on-road parking, there are problems such as parking confusion and illegal occupation of road resources, which affect the road capacity. Therefore, this paper takes Harbin residential area as an example to explore and explore on-road parking management strategy. Firstly, the status of on-road parking in residential areas is examined, and the deficiencies of on-road parking management in residential areas are analyzed. Referring to advance management experience and mode of on-road parking in residential areas abroad, and combined with the actual parking situation of Harbin residential areas, this paper puts forward the corresponding optimization strategy of on-road parking management.